His narrator and the implicit reader An applied study in the short story, The Settlement (Journal of the College of Basic Education, 2023)
The concept of (narrator) is defined in some dictionaries as: ((the listener).The reader to whom the story is directed, who is not just an individual to whom the story is told; As it shouldThe text includes indications that the story is actually directed to a specific (audience) or reader.It means the necessity to include in the text what suggests .. that)) (1) and it is my opinion that does not differentiate between the reader and the narratorIt has an imaginary linguistic entity within the narrative context.While others, including Ari (Gerald Prince), confirm that in the dictionaryNarrative terms: ((A pure narrative structure that should not be confused with the recipient orA true reader can read many narratives (each of which has its own narrative).different) or the same narration (which always contains the same set of narrators)Which can be read by a different group of real readers)) (2). And apparently I seeThe narrator deviates with an aura of privacy that distinguishes him from the forms of the implicit or real reader.